Structural changes in the employment structure of India in 2012-2020: Job upgrading or polarization? - Sudipa Sarkar; Sergio Torrejón Pérez (European Commission, Joint Research Centre (JRC), 2023)
This paper analyses employment growth across occupations and sectors in India for the period that goes from 2011-12 to 2019-20. Using data from the National Sample Survey Organisation and the Periodic Labour Force Survey, this study finds evidence of mid-upgrading (relatively higher employment growth in low-mid paid and high-paid jobs) in India during the study period, where jobs are ranked using median daily wages in 2011-12. A decomposition analysis reveals that this pattern is due to the employment growth in jobs in Construction, Wholesale & retail trade, and Transport, storage and communication industries in India. The study also finds a reduction in the employment share of routine task intensive occupations along with a growth in employment in non-routine task intensive occupations (both manual and cognitive) in both rural and urban India.
Keywords: 330; employment change; job polarization; technological change; India